RANCANG BANGUN DAN UJI KINERJA DESTILATOR ELEKTRIK SEBAGAI ALAT DESTILASI PADA PROSES PEMBUATAN BIOETHANOL - Wahyu Sehwantoro; Fifin Hindarti; Mawar Oktivina (Institut Sains dan Teknologi Nasional, 2021)
Reserves of fuel oil, especially those from fossil fuels, are dwindling, while the people's need for fuel oil is increasing. Dependence on fossil fuels needs to be addressed immediately. So it is necessary to develop renewable energy sources as alternative energy to replace fuel oil. One of them is by utilizing bioethanol as an alternative. The process of making bioethanol involves a distillation process. In this study, the design and performance test of an electric distillation apparatus was carried out by utilizing molasses as a raw material for making bioethanol. The aim is to determine the quality of the alcohol content in bioethanol which is processed using an electric distillation apparatus. Electrical distillator testing includes functional tests and performance tests. Functional testing is done by testing the components used in the tool so that it can be seen whether the tool is functioning properly. Meanwhile, the performance test of the electric distillator is an automatic performance test of a tool to produce bioethanol. The performance test procedure of the electric distillator was carried out using a bimetallic thermostat of 76ºC and 85ºC, to measure the distillation time and determine the alcohol content in bioethanol. From the results of the study, it was found that for an electric distillator that uses a bimetallic thermostat of 76˚C, the processing time of 70.43 hours produces bioethanol with an alcohol content of 61.7% and an electric distillator that uses a bimetallic thermostat of 85˚C with a processing time of 0.56 hours to produce bioethanol. with an alcohol content of 35%.